Crystal structure of a lectin from Canavalia maritima (ConM) in complex with trehalose and maltose reveals relevant. mutation in ConA-like lectins - Delatorre, P.; Rocha, BAM; Gadelha, CAA; Santi-Gadelha, T.; Cajazeiras, J. B.; Souza, E. P.; Nascimento, K. S.; Freire, V. N.; Sampaio, A. H.; Azevedo, W. F.; Cavada, B. S. (Elsevier B.V., 2006)
The crystal structure of Canavalia maritima lectin (ConM) complexed with trehalose and maltose revealed relevant point mutations in ConA-like lectins. ConM with the disaccharides and other ConA-like lectins complexed with carbohydrates demonstrated significant differences in the position of H-bonds. The main difference in the ConM structure is the replacement of Pro202 by Ser202, a residue that promotes the approximation of Tyr12 to the carbohydrate-binding site. The O-6' of the second glucose ring in maltose interacts with Tyr12, while in trehalose the interaction is established by the O-2' and Tyr12, explaining the higher affinity of ConM for disaccharides compared to monosaccharides. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: lectins; Canavalia maritima; Crystal structure; mutation